156k views
1 vote
HELPPPPPPPPPPPPPPPPPPPPPP

HELPPPPPPPPPPPPPPPPPPPPPP-example-1

1 Answer

10 votes

Answer:

A. x= 3, y= -2

Explanation:

[2] 2x= 4y+14

[1] 3y+5x=9

Solve equation [2] for the variable x

[2] 2x = 4y + 14

[2] x = 2y + 7

// Plug this in for variable x in equation [1]

[1] 5•(2y+7) + 3y = 9

[1] 13y = -26

// Solve equation [1] for the variable y

[1] 13y = - 26

[1] y = - 2

// By now we know this much :

x = 2y+7

y = -2

// Use the y value to solve for x

x = 2(-2)+7 = 3

good luck, I hope this helps!!!

User Algeroth
by
5.2k points